RETRACTED: Studying the condition of tungsten-containing man-made waste in the territory of Uzbekistan - Khasanov Adkham; Khasanov Ulugbek; Toshtemirov Umarali; Abdurakhmanov Davronbek; Melnikova Tatyana (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 538, 00001 (2024), https://doi.org/10.1051/e3sconf/202453800001